Histone H3K27 methyltransferase Ezh2 represses Wnt genes to facilitate adipogenesis - Wang, Lifeng (National Academy of Sciences, 2010)
Wnt/β-catenin signaling inhibits adipogenesis. Genome-wide profiling studies have revealed the enrichment of histone H3K27 methyltransferase Ezh2 on Wnt genes. However, the functional significance of such a direct link between the two types of developmental regulators in mammalian cells, and the role of Ezh2 in adipogenesis, remain unclear. Here we show Ezh2 and its H3K27 methyltransferase activity are required for adipogenesis. Ezh2 directly represses Wnt1, -6, -10a, and -10b genes in preadipocytes and during adipogenesis. Deletion of Ezh2 eliminates H3K27me3 on Wnt promoters and derepresses Wnt expression, which leads to activation of Wnt/β-catenin signaling and inhibition of adipogenesis. Ectopic expression of the wild-type (WT) Ezh2, but not the enzymatically inactive F667I mutant, prevents the loss of H3K27me3 and the defects in adipogenesis in Ezh2(−/−) preadipocytes. The adipogenesis defects in Ezh2(−/−) cells can be rescued by expression of adipogenic transcription factors PPARγ, C/EBPα, or inhibitors of Wnt/β-catenin signaling. Interestingly, Ezh2(−/−) cells show marked increase of H3K27 acetylation globally as well as on Wnt promoters. These results indicate that H3K27 methyltransferase Ezh2 directly represses Wnt genes to facilitate adipogenesis and suggest that acetylation and trimethylation on H3K27 play opposing roles in regulating Wnt expression.